Senescent immune cells in the tumor microenvironment: emerging insights into cancer immunotherapy resistance - Gao, Duolun; Kan, Peiyan; He, Yanjie; Sun, Siyu; Tang, Lei; Yang, Fan (Frontiers in Immunology, 2025)
Cancer remains a leading cause of mortality worldwide, with rising incidence and death rates continuing to rise. While conventional treatments such as surgery, radiotherapy, and chemotherapy form the backbone of cancer care, they are often limited by adverse effects, recurrence risk, and incomplete tumor eradication. Tumor immunotherapy—particularly immune checkpoint inhibitors and chimeric antigen receptor (CAR) T cell therapy—has emerged as a transformative approach by activating and reprogramming anti-tumor immune responses. Despite these advances, significant challenges persist, including limited response rates to checkpoint inhibitors, the immunosuppressive nature of the tumor microenvironment (TME), and resistance mechanisms employed by tumor cells. Growing evidence suggests that immune cell senescence is a critical contributor to TME-driven immunosuppression. Senescent immune cells exhibit functional decline, elevated expression of inhibitory immune checkpoint molecules, and increased secretion of pro-inflammatory cytokines, collectively impairing anti-tumor immunity and reducing the efficacy of immunotherapy. This review highlights the role of immune cell senescence in shaping the immunosuppressive TME and driving resistance to immunotherapy. It further discusses emerging therapeutic strategies that combine immunotherapy with senescence-targeting interventions, aiming to provide novel insights into the development of more effective cancer treatment strategies.